Linac-based stereotactic radiosurgery and fractionated stereotactic radiotherapy for vestibular schwannomas: Comparative observations of 139 patients treated at a single institution - Putipun Puataweepong (2018)
Stereotactic radiosurgery (SRS) and fractionated stereotactic radiotherapy (SRT) have been recognized as an alternative to surgery for small to medium sized vestibular schwannoma (VS). This study analysed and compared the outcomes of VS treated with the first Thailand installation of a dedicated Linac-based stereotactic radiation machine using single-fraction radiosurgery (SRS), hypofraction stereotactic radiotherapy (HSRT) and conventional fraction stereotactic radiotherapy (CSRT). From 1997 to 2010, a total of 139 consecutive patients with 146 lesions of VS were treated with X-Knife at Ramathibodi hospital, Bangkok, Thailand. SRS was selected for 39 lesions (in patients with small tumors ≤3 cm and non-serviceable hearing function), whereas HSRT (79 lesions) and CSRT (28 lesions) were given for the remaining lesions that were not suitable for SRS. With a median follow-up time of 61 months (range, 12-143), the 5-year local control rate was 95, 100 and 95% in the SRS, HSRT and CSRT groups, respectively. Hearing preservation was observed after SRS in 75%, after HSRT in 87% and after CSRT in 63% of the patients. Cranial nerve complications were low in all groups. There were no statistically significant differences in local control, hearing preservation or complication between the treatment schedules. In view of our results, it may be preferable to use HSRT over CSRT for patients with serviceable hearing because of the shorter duration of treatment. © 2013 The Author 2013. Published by Oxford University Press on behalf of The Japan Radiation Research Society and Japanese Society for Therapeutic Radiology and Oncology.